The Best Medicine? The Nature Of Humour And Its Significance For The Process of Psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
In this paper the theoretical landscape of humour will be surveyed, giving the reader a glimpse into the origin, evolution, and meaning of the complex and ubiquitous phenomenon of humour. The significance of humour for the practice of psychotherapy is also discussed.
Keywords: Humour; laughter; evolution; resolution; subversion; play; creativity; power